Competencies of a deaf educator and deaf speech and language therapist in the diagnostic and therapeutic process of a child with hearing impairment - MARCINIAK-FIRADZA, RENATA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Renata Marciniak-Firadza, Competencies of a deaf educator and deaf speech and language therapist in the diagnostic and therapeutic process of a child with hearing impairment. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 297-331. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https:// doi.org/10.14746/ikps.2019.25.13 The specificity of the cognitive processes of a child with hearing impairment, and the need to apply appropriate methods and means of teaching, requires participation of a properly prepared specialist in the field of remedial and educational, preventive and therapeutic work in the didactic process. The manifestation of not only theoretical reflection on the profession of teacher and speech and language therapist, but also the effect of practical searches related to the vocational education and training of educators and speech and language therapists, as well as the assessment of their work, is the issue of professional competencies of a deaf educator and deaf speech and language therapist in the diagnostic and therapeutic process of a child with hearing impairment. Competence is understood in the article in two ways: as a range of knowledge, skills, predispositions and as a range of qualifications.